Kombinasi Breast Care dan Acupressure Points for Lactation untuk Meningkatkan Kecukupan Air Susu Ibu (ASI) bagi Bayi - Nana Usnawati; Astin Nur Hanifah; Triana Septianti Purwanto (FORIKES, 2022)
Acupressure points for lactation is to provide acupressure on specific meridian points in the breast area for optimization of prolactin and oxytocin receptors. The purpose of this study was to analyze the effectiveness of the combination method of